2023
DOI: 10.7150/thno.85084
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pleural microenvironment niche and cancer transition using single-cell RNA sequencing in EGFR-mutated lung cancer

Abstract: Background: Lung cancer is associated with a high mortality rate and often complicated with malignant pleural effusion (MPE), which has a very poor clinical outcome with a short life expectancy. However, our understanding of cell-specific mechanisms underlying the pathobiology of pleural metastasis remains incomplete. Methods: We analyzed single-cell transcriptomes of cells in pleural effusion collected from patients with lung cancer and congestive heart failure (as a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Many studies have suggested that PDCs may enhance an antitumor immune response by using TLR7 and TLR9 agonists [17][18][19]. However, others believe that pDCs may exhibit a pro-tumorigenic or immunoregulatory feature in tumor [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that PDCs may enhance an antitumor immune response by using TLR7 and TLR9 agonists [17][18][19]. However, others believe that pDCs may exhibit a pro-tumorigenic or immunoregulatory feature in tumor [20,21].…”
Section: Discussionmentioning
confidence: 99%